The Influences of Metformin on Prostate in Terms of PSA Level and Prostate Volume - Atalay, Eray; Demir, Aslan; Eroglu, Hüseyin Avni (Urology Journal, 2020)
Purpose: The effects of metformin on prostate volume and prostate-specific antigen (PSA) were investigated. Materials and Methods: We enrolled 384 newly diagnosed diabetes mellitus (DM) patients and 152 controls all of whom were >50 years into our prospective cross-sectional observational study. The first group contained patients receiving metformin only, the second group patients were taking a mixture of medications, including metformin plus other oral anti-diabetics, and the third was the control group. Before beginning treatment, body mass indices (BMI) of all cases were obtained. Prostate volumes were evaluated using transabdominal ultrasonography at the sixth and twelfth months. Insulin, glycosylated hemoglobin (HbA1C), insulin sensitivity index (ISI), insulin-rich growth factor (IGF-1), PSA, free PSA, and total testosterone levels were measured. Results: The differences in BMI between the first and third groups were statistically significant (P < 0.05). There were no statistical differences among the groups in terms of prostate volumes (P > 0.05). The differences between the groups for insulin, HbA1C, ISI, IGF-1 (somatomedin), PSA, free PSA, and total testosterone levels were not statistically significant (P > 0.05). Free PSA and total testosterone levels in groups 1 and 2 were not statistically different at the beginning of treatment and the sixth month (p >0.05), but within groups 1 and 2, only PSA levels were different at the start of the study until completion. No differences were seen in the third group. Conclusion: Metformin appears to cause a decrease in PSA levels. The mechanism and any effects on prostate tissue will be studied in future randomized, prospective studies.